Severe Juvenile-Onset Systemic Lupus Erythematosus: A Case Series-Based Review and Update - Sergi Huerta-Calpe; Ignacio Del Castillo-Velilla; Aida Felipe-Villalobos; Iolanda Jordan; Lluïsa Hernández-Platero (MDPI AG, 2023)
Juvenile-onset systemic lupus erythematosus (jSLE) is a multisystemic disease diagnosed in young patients based on the clinical criteria of the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR). The importance of this condition lies in its greater aggressiveness compared with lupus diagnosed during adulthood (aSLE). Management, which is based on supportive care and immunosuppressive drugs, aims to reduce the overall disease activity and to prevent exacerbation. Sometimes the onset is accompanied by life-threatening clinical conditions. In this paper, we introduce three recent cases of jSLE that required admission to the Pediatric Intensive Care Unit (PICU) of a Spanish pediatric hospital. This manuscript aims to review some of the main complications associated with jSLE, such as diffuse alveolar hemorrhage, cerebral vasculitis, or an antiphospholipid syndrome; these are life-threatening conditions but they have a chance of favorable prognosis if treated early and aggressively.